Number order in addition affects cognitive effort: evidence from mental arithmetic tasks - Omid Khatin-Zadeh; Danyal Farsani; Zahra Eskandari; Arash Ghahraman; Jiayong He; Jiayong He; Hassan Banaruee (Frontiers in Psychology)
In this study, our aim was to find out how order of numbers in the arithmetic operation of addition affects cognitive effort of mental processing. We presented two sets of addition questions (a + b) to a group of participants. In one set of questions, the first number of each item was larger than the second number (a > b). In another set of questions, the first number was smaller than the second number (a < b). The participants were asked to answer each item within a period of 12 seconds. The results showed that when the first number was larger than the second number, participants provided more correct answers and were faster in giving correct answers. Two explanations are discussed for these results. Finally, it is concluded that the property of commutativity of addition does not mean that performing that operation in various situations involves the same level of cognitive effort.